Theoretical foundations of the Home Psychological Care Strategy for the prevention and treatment of cancer - Yudania Perez Rondon; Aimee Vázquez Llanos; Pablo Hernández Figaredo; Norbis Díaz Campos (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Psychological work related to the fight and control of cancer is becoming increasingly important, taking into account that it is declared among the leading causes of death worldwide. The present scientific work aims to establish, from a theoretical point of view, the Home Psychological Care Strategy aimed at improving the prevention and treatment of cancer in the San Juan de Dios Popular Council, from a biopsychosocial approach, with an emphasis on Comprehensive home care for cancer patients and their families. In addition, the different stages that comprise it, their objectives and the actions that were carried out are exposed. For the pilot study, medical office 29 of the health area belonging to the José Martí Pérez University Polyclinic, in Camagüey, was selected. The current results derive from the research project Socio-psychological intervention strategy for the prevention and treatment of cancer in primary health care, which manages the Center for the Development of Social and Humanistic Sciences in Health, of the University of Medical Sciences of Camagüey and whose execution process corresponds to the period 2016-2021.